Smart Face Attendance System Using Deep Face Integration for BCB Berhad Kluang - MUHARAM, NUR AIN; ABD WARIF, NOR BAKIAH (Applied Information Technology And Computer Science, 2026)
An attendance system is a method used to record and monitors individual presences. BCB Berhad is a property development company which is using a traditional punch card system for 20 years but faces several challenges includes human error, time consuming hours calculation and buddy punching. Smart Face Attendance System Using Deep Face Integration is introduce align with the needs of BCB Berhad target clients. This system deploys face recognition use DeepFace library that includes Python integrated with PHP in Visual Studio Code. Object-Oriented approach is use to develop the system includes analysis, design, implementation, testing and maintenance phases. The outcome is to create a web-based system with security features and accurate face recognition. Thus, the system bring benefit to all user by automatically matching faces, recording attendance and calculating daily working hours.